Assessing variation in bacterial composition between the rhizospheres of two mangrove tree species - Gomes, Newton C. M.
This study aimed to determine to what extent roots from the common mangrove tree species Avicennia schaueriana and Laguncularia racemosa are able to impose a selective force on the composition of sediment bacterial communities in mangrove intertidal sediments using barcoded pyrosequencing analysis of 16S rRNA gene fragments (V4 hyper-variable region). The novel results showed that root systems of A.schaueriana and L.racemosa are associated with increased bacterial dominance, lower richness and compositional shifts of sediment bacterial communities. The proportion of OTUs (operational taxonomc units) belonging to the orders Rhizobiales and Vibrionales were enriched in rhizosphere samples from both plant species and sulphur-reducing bacteria (SRB) belonging to the order Desulfobacterales and Desulfuromonadales were enriched in the rhizosphere of A.schaueriana. In addition, Clostridium and Vibrio populations were more abundant in different mangrove rhizospheres. A.schaueriana and L.racemosa roots appear to be able to impose a selective force on the composition of mangrove sediment bacterial communities and this phenomenon appears to be plant species specific. Our findings provide new insights into the potential ecological roles of bacterial guilds in plant-microbe interactions and may aid rhizoengineering approaches for replanting impacted mangrove areas.